A Study on Nomophobia - Mobile Phone Dependence, Among Students of a Medical College in Bangalore - Pavithra MB; Suwarna Madhukumar; Mahadeva Murthy TS (National Journal of Community Medicine, 2015)
Background: Smart phones today have become an important part of our techno-culture, especially among the younger population. Discomfort, anxiety, nervousness or anguish caused by being out of contact with a mobile phone is termed as "Nomophobia"- no mo- bile phobia. Nomophobia is on the rise across the globe.